2013
DOI: 10.1590/1516-3180.20131315t2
|View full text |Cite
|
Sign up to set email alerts
|

Immersion in water in labour and birth

Abstract: BACKGROUND: Enthusiasts suggest that labouring in water and waterbirth increase maternal relaxation, reduce analgesia requirements and promote a midwifery model of care. Critics cite the risk of neonatal water inhalation and maternal/neonatal infection. OBJECTIVES: To assess the evidence from randomised controlled trials about immersion in water during labour and waterbirth on maternal, fetal, neonatal and caregiver outcomes. METHODS: COMMENTSIt is already known by obstetricians and midwives that warm bath im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 1 publication
3
74
1
3
Order By: Relevance
“…A systematic review of 3,243 women suggested that the use of this practice during the first stage of labor reduced the use of epidural anesthesia, with no adverse effects to either the mother or baby. The immersion bath was also associated with greater satisfaction with the childbirth experience (20) .…”
Section: Category Cmentioning
confidence: 91%
“…A systematic review of 3,243 women suggested that the use of this practice during the first stage of labor reduced the use of epidural anesthesia, with no adverse effects to either the mother or baby. The immersion bath was also associated with greater satisfaction with the childbirth experience (20) .…”
Section: Category Cmentioning
confidence: 91%
“…There are also studies that have reported the disadvantages associated with water birth which include maternal and neonatal infections, as well as the possibility of respiratory problems for the newborn (7,8). Cluett and Burns in a review of 11 trials concluded that water immersion during the first stage of labour reduced the use of epidural/spinal analgesia, but there was limited data for other outcomes related to water use during the first and second stages of labour (9). They also stated that there was no evidence of increased adverse effects on the fetus/neonate or woman from labouring in water (9).…”
Section: Abstract öZetmentioning
confidence: 99%
“…The early use of the warm bath (when dilatation is less than five cm) is related to increased use of analgesia when compared to women who use the intervention when dilatation greater than five cm. (7) The warm bath provides relief from pain and anxiety, increases the comfort, and provides positive feelings during the labor, (5,6) especially when combined with perineal exercise with the Swiss ball. (2) Its use facilitates a professional approach when patient-centered care is provided, which results in benefits for labor progress.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Its use facilitates a professional approach when patient-centered care is provided, which results in benefits for labor progress. (7) The use of the Swiss ball to perform perineal exercises during labor is an auxiliary therapy in the obstetrical practice that promotes comfort and pain relief, labor progression, and favors the vertical position. (15) This intervention provides less need for medication and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation